2017
DOI: 10.1088/1674-1056/26/4/047102
|View full text |Cite
|
Sign up to set email alerts
|

First principles investigation of protactinium-based oxide-perovskites for flexible opto—electronic devices

Abstract: The structural, elastic, mechanical, electronic, and optical properties of KPaO 3 and RbPaO 3 compounds are investigated from first-principles calculations by using the WIEN2k code in the frame of local density approximation (LDA) and generalized gradient approximation (GGA). The calculated ground state quantities, such as lattice constant (a 0 ), ground state energy (E), bulk modulus (B), and their pressure derivative (B p ) are in reasonable agreement with the present analytical and previous theoretical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The perovskites are mainly found as oxides having the general formula ABX 3 where A and B are cations, and X is an anion, usually oxides or halogens. In contrast, A is an alkali or alkaline element, and B can be either a transition or inner transition element, sometimes from the s block also [9,10]. Recently halide perovskites have been in the leading position because of their peculiar properties, which facilitate their applications in photovoltaics, optoelectronics, spintronics, radio isotope generators (RTG's).…”
Section: Introductionmentioning
confidence: 99%
“…The perovskites are mainly found as oxides having the general formula ABX 3 where A and B are cations, and X is an anion, usually oxides or halogens. In contrast, A is an alkali or alkaline element, and B can be either a transition or inner transition element, sometimes from the s block also [9,10]. Recently halide perovskites have been in the leading position because of their peculiar properties, which facilitate their applications in photovoltaics, optoelectronics, spintronics, radio isotope generators (RTG's).…”
Section: Introductionmentioning
confidence: 99%
“…Designing new perovskites as well as tailoring available perovskites to obtain optimized properties is still an active research area. In nature perovskites are mainly found as oxides having general formula ABX 3 where A and B are cations and X is an anion usually oxides or halogens whereas A is alkali or alkaline element and B is either transition or inner transition element, sometimes from s block also 8 , 9 . Currently, extensive research is perceived rigorously either theoretically or experimentally to see these functional alloys for many perspective needs.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The unique versatility of such an oxide perovskite crystal structure finds novel functionalities in material science and enormous potential for novel device applications. [5,6] Shpanchenko et al [7] and Belik et al [8] reported that such materials undergo a unique transformation from metalliclike behavior to and insulator when they are exposed to high external pressure. Among transition metal oxides, AVO 3 (3d 1 electronic configuration) is a potential candidate for high-temperature solid oxide fuel cells, multiferroic devices and show novel applications in the field of high T c superconductivity.…”
Section: Introductionmentioning
confidence: 99%